2016
DOI: 10.1155/2016/6058147
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages and Neutrophils in Tumor Microenvironment

Abstract: Distinct tumor microenvironment forms in each progression step of cancer and has diverse capacities to induce both adverse and beneficial consequences for tumorigenesis. It is now known that immune cells can be activated to favor tumor growth and progression, most probably influenced by the tumor microenvironment. Tumor-associated macrophages and tumor-associated neutrophils can exert protumoral functions, enhancing tumor cell invasion and metastasis, angiogenesis, and extracellular matrix remodeling, while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
553
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(569 citation statements)
references
References 107 publications
5
553
1
10
Order By: Relevance
“…examination for patients, and neutrophil counts are commonly used to evaluate a patient's inflammatory state in clinical practice. Tumor neutrophil infiltration has also been found to be associated with the promotion of inflammation, contributing to tumor progression (29). Therefore, we hypothesized that the peripheral neutrophil count could be a biomarker indicative of the tumor inflammatory microenvironment in HCC and the efficacy of sorafenib treatment.…”
Section: Univariate Analysismentioning
confidence: 99%
“…examination for patients, and neutrophil counts are commonly used to evaluate a patient's inflammatory state in clinical practice. Tumor neutrophil infiltration has also been found to be associated with the promotion of inflammation, contributing to tumor progression (29). Therefore, we hypothesized that the peripheral neutrophil count could be a biomarker indicative of the tumor inflammatory microenvironment in HCC and the efficacy of sorafenib treatment.…”
Section: Univariate Analysismentioning
confidence: 99%
“…In this report, the amount of platelet mRNA that was required was only 100-500 pg [7]. Although the mechanism of platelet-to-tumor changes in the peripheral blood after contact with tumor cells remains unclear, the study has the disadvantage of having a small sample size, and the presence of platelet mRNA is unstable over 48 hours, such studies have confirmed that normal cells in the peripheral blood that have been in contact with tumor cells in the tumor microenvironment facilitate early tumor diagnosis [6].…”
Section: Progress and Problems In Liquid Biopsymentioning
confidence: 67%
“…Neutrophils account for 50%-70% of total leukocytes in the peripheral blood (4.0-10.0 x 10^9/L). It is generally considered that during the development of various cancers, including oral cancer, inflammatory factors that are released by tumor cells, including reactive oxygen species and IL-8, may recruit peripheral blood neutrophils to local tumor microenvironments [7][8][9]. This may play important roles in promoting tumor proliferation and metastasis [10,11].…”
Section: The Possible Role Of Neutrophils In Liquid Biopsymentioning
confidence: 99%
“…Проаналізований вміст лейкоцитів, лімфоцитів, нейтрофільних гранулоцитів і тромбоцитів у крові 105 хворих з пухлинами головного мозку, в тому числі 67 -нейроектодермального, 20 В опухолевом процессе активно участвуют клетки иммунной системы, которые могут как подавлять, так и стимулировать рост опухоли [1][2][3][4]. В последнее де-сятилетие исследователи обращают особое внимание на изучение роли в онкогенезе клеток врожденного иммунитета, в частности, НГ, натуральных киллеров, дендритных клеток.…”
Section: вміст клітин вродженого та набутого імунітету у периферійнійunclassified
“…При количестве Тр более 400х10 9 в 1 л отмечено уменьшение 5-летней ремиссии у больных раком пищевода и, наоборот, уменьшение количества Тр до 200х10 9 в 1 л способствовало увели-чению показателей 5-летней выживаемости больных [5][6][7]. Тр и факторы комплемента играют важную роль в опухользависимом воспалении, привлекая макрофаги и НГ в очаг опухоли [3][4][5].…”
Section: вміст клітин вродженого та набутого імунітету у периферійнійunclassified